Experimental investigation of strength, stiffness and drift capacity of rubble stone masonry walls. (10th August 2020) - Rezaie, Amir; Godio, Michele; Beyer, Katrin
Highlights: Axial load and shear span affect the drift capacity of stone masonry walls. Splitting cracks between the wall leaves play a key role in the collapse mechanism. The drift at a 50% drop in force yields a biased estimate for drift at collapse. Abstract: There is limited available research on rubble stone masonry walls, which are vulnerable under seismic loading. This paper presents an experimental campaign of cyclic shear compression tests on six large-scale walls of this topology. The effect of the axial load and shear span ratio on the wall behaviour, notably on the wall stiffness, strength, and drift capacity, was investigated. It was found that the drift at crack onset is only half of that in previous campaigns on stone masonry walls, likely because one face of each wall was plastered, making the damage more visible. Additionally, splitting cracks opening between the wall leaves appear to play a key role in the collapse mechanism. Finally, testing the walls up to the loss of their axial-load-bearing capacity provides new input for the collapse risk analysis of stone masonry buildings.